Estonia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This report describes recent economic developments in the Republic of Estonia. The report highlights that after a cumulative decline of almost 30 percent in 1992-93, real GDP is estimated to have increased in 1994. Data on the composition of GDP by sector reflect the continuing adjustment of Estonia's economy to fundamental systemic change and the institutional disruption of former production and trade patterns. The importance of the services sector has risen substantially, and is now estimated to account for more than 60 percent of GDP.